An ancient DNA Pacific journey: a case study of collaboration between archaeologists and geneticists. Issue 4 (8th August 2019) - Spriggs, Matthew; Reich, David
ABSTRACT: We present a case-study of a collaboration between archaeologists and geneticists that has helped settle a long-standing controversy and opened up new research questions for the Pacific region. The work provided insights into the history of human settlement and cultural changes in Vanuatu in the western Pacific, which in turn shed light on the origins of the cultural and linguistic diversity that characterizes the archipelago. Close interdisciplinary collaborations like this maximize the potential of ancient DNA to contribute to our understanding of the past and advance the scholarship of practitioners in both disciplines.